2019
DOI: 10.1021/jacs.8b10904
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Iron Oxide-Induced Macrophage Activation: The Impact of Composition and the Underlying Signaling Pathway

Abstract: Iron oxide nanoparticles (IONPs) have emerging anti-cancer applications via polarizing tumor-associated macrophages from tumor-promoting phenotype (M2) to tumor-suppressing phenotype (M1). However, the underlying mechanism and structure-function relationship remain unclear. We report magnetite IONPs are more effective compared to hematite in M1 polarization and tumor suppression. Moreover, magnetite IONPs specifically rely on interferon regulatory factor 5 signaling pathway for M1 polarization and downregulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
148
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(151 citation statements)
references
References 36 publications
3
148
0
Order By: Relevance
“…There is a complex interdependence between the physicochemical properties of nanomaterials and their catalytic activity. [ 41,42 ] Regarding iron oxide NPs, the surface Fe 2+ ions play an important role for their peroxidase‐like activity. [ 17 ] Therefore, Fe 2 O 3 NPs showed an inferior catalytic activity compared to Fe 3 O 4 NPs (Figure 6b) due to the diminished amount of Fe 2+ ions on the surface of iron oxide NPs.…”
Section: Discussionmentioning
confidence: 99%
“…There is a complex interdependence between the physicochemical properties of nanomaterials and their catalytic activity. [ 41,42 ] Regarding iron oxide NPs, the surface Fe 2+ ions play an important role for their peroxidase‐like activity. [ 17 ] Therefore, Fe 2 O 3 NPs showed an inferior catalytic activity compared to Fe 3 O 4 NPs (Figure 6b) due to the diminished amount of Fe 2+ ions on the surface of iron oxide NPs.…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with these findings, in a mouse model of sickle disease, hemolysis and macrophage heme-iron accumulation trigger a proinflammatory phenoytpe in hepatic macrophages (Vinchi et al., 2016). In cancer, iron-loaded tumor-associated macrophages adopt a pro-inflammatory phenotype that can directly kill tumor cells (Costa da Silva et al., 2017), and the usage of iron oxide nanoparticles is an attractive avenue in cancer immunotherapy through the modulation of macrophage activity (Gu et al., 2019, Zanganeh et al., 2016). In summary, the findings from all of the above-mentioned studies converge toward a macrophage polarization profile resulting from prolonged exposure to iron in the tissue microenvironment, correlating with a pro-inflammatory (M1-like) phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that SPIONs affect cytokine production in immune cells, including macrophages (Hsiao et al., 2008; Yeh et al., 2010). In addition, several reports have shown that SPIONs induce a phenotypic shift in macrophages from M2 to M1 (Laskar et al., 2013; Gu et al., 2019). Therefore, we evaluated the effect of magnetic lipoplexes on cytokine and NO production in RAW264 cells.…”
Section: Discussionmentioning
confidence: 99%